A influência dos mecanismos de aprendizagem na trajetória de acumulação das capacidades tecnológicas no Rioprevidência entre 2008 e 2015 - Sá, Guilherme Saraiva de (2016)
The main reason for this study is to observe the influence that the learning process have on the accumulation of technological capabilities between the period of 2008 to 2015 regarding the Rio de Janeiro single Social Security Fund (Rioprevidencia). For the study execution were seized two models built from Figueiredo (2015) capable of identify the process of the accumulation of technological capabilities based on learning process on private institutions. The adaptation proposal of those mechanisms into the reality of this fund and to present the influence that they have on technological capabilities was possible after the exams of those mechanisms types and characteristics and the evolution found on the technological capabilities levels showed along the proposed time period. Those analyses were made based on evidences collected from documentary researches, direct observation and semi structured interviews. Like this we can manage to identify in the end of the study, as similar as what happens at private institutions changes that those knowledge mechanisms retention generates on the Rioprevidencia accumulation of technological capabilities. It is expected along this empirical study to introduce this theme on the rise inside the Rio de Janeiro Government, showing the importance regarding the follow up of those variables in a near future, making its management to be used with due importance at the public sector.